Exploration of Nonlinear Optical Properties of Triphenylamine-Dicyanovinylene Coexisting Donor-π-Acceptor Architecture by the Modification of π-Conjugated Linker - Khan, Muhammad Usman; Khalid, Muhammad; Asim, Sumreen; Momina,; Hussain, Riaz; Mahmood, Khalid; Iqbal, Javed; Akhtar, Muhammad Nadeem; Hussain, Amjad; Imran, Muhammad; Irfan, Ahmad; Ali, Akbar; et al. (Frontiers in Materials, 2021)
High-tech electronic, optics, and storage devices require organic compounds with nonlinear optical (NLO) properties. This study designed D-π-A based dyes with donor triphenylamine (TPA) and acceptor dicyanovinylene (DCV) species by structurally modifying π-conjugated linkers. Our density functional theory (DFT) computations analyzed the impact of structural variations on the nonlinear optical (NLO) response of newly designed dyes. The B3LYP/6-31G(d,p) level determined the quantic chemical insights: frontier molecular orbital (FMOs), natural bond orbitals (NBOs) and nonlinear optical (NLO) properties of the designed dyes (DPTM-1 to DPTM-12). UV-Vis analysis based on the TD-DFT/CAM-B3LYP/6-311+G(d,p) level explored the optoelectronic properties. DPTM-1 and DPTM-5 showed the highest red-shifted absorption band at 519 and 506 nm. NBO analysis shows that DPTM-1 to DPTM-12 dyes have positive values for all donors (D) and π-spacers but negative values for acceptors (A). The π-spacers act as a conveyer between donor and acceptor moieties; thus, electrons were transferred smoothly from D to A units, which resulted in a charge separation state. Our calculations show the extent of NLO response in terms of electronic transitions, polarizability <α> and first hyperpolarizability (β) values. The highest value of βtotal was 110509.23 a.u. manifested in DPTM-6 due to 2,5-dimethyloxazole as a 2nd-π-linker, twice that of R (66275.95 a.u.). Also, DPTM-6 and DPTM-8 exhibit the lowest energy band gap of 2.06 and 2.04 eV, respectively. In short, all DPTM-1 to DPTM-12 dyes manifested maximum absorption, lowest energy band gap, greater charge transfer from donor to the acceptor and better first hyperpolarizability values as compared to the R and showed good NLO response. The present work represents new compounds with remarkable NLO properties and their applications in modern high-tech devices.